2014
DOI: 10.4103/2230-973x.143114
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of moxifloxacin loaded chitosan-dextran nanoparticles for topical instillation into eye: In-vitro and ex-vivo evaluation

Abstract: Introduction:Management of ocular surface disease by conventional formulation is limited by poor residence of drug at cul-de-sac of eye. To overcome this limitation, prolonged released mucoadhesive chitosan (CS)–dextran sulfate (DS) nanoparticles (NPs) were investigated for the prolonged topical ophthalmic delivery of moxifloxacin (Mox).Methods:Formulation was optimized by 3-factors (CS, DS, and Mox concentration), 3-levels (−1, 0, +1) Box-Behnken design. Optimized formulation was characterized for various in-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…The morphology of these vesicles is depicted in Figure 3 A–C, respectively. Previously, Kaskoos (2014) reported the size of moxifloxacin-loaded chitosan–dextran nanoparticles as 279.18 nm, with a good polydispersity index of 0.367 [ 25 ]. In another study, Sohrabi et al (2016) reported the size of chitosan gel-embedded moxifloxacin niosomes to be around 290 nm [ 26 ], suggesting that this formulation has a small size and will show a good therapeutic response in vitro and in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…The morphology of these vesicles is depicted in Figure 3 A–C, respectively. Previously, Kaskoos (2014) reported the size of moxifloxacin-loaded chitosan–dextran nanoparticles as 279.18 nm, with a good polydispersity index of 0.367 [ 25 ]. In another study, Sohrabi et al (2016) reported the size of chitosan gel-embedded moxifloxacin niosomes to be around 290 nm [ 26 ], suggesting that this formulation has a small size and will show a good therapeutic response in vitro and in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…They observed an efficient NPs distribution in lens and retina. Similarly, chitosan-dextran NPs have been employed to deliver the antibiotic moxifloxacin that has been retained for a long time in vivo thanks to the mucoadhesive properties of NPs [132].…”
Section: Natural Hydrogels: Chitosan Nps (Chnps)mentioning
confidence: 99%
“…The authors conclude that this suspension was more effective than the commercially marketed product MoxiGram ® . MX antibiotic was also encapsulated into Ch–dextran sulfate (DS) NPs [ 18 ] and the efficiency of the formulation was tested in vitro and ex vivo against S. aureus and P. aeruginosa . The results revealed that the use of NPs exhibits a prolonged drug release profile with significantly high transcorneal permeation and high corneal retention.…”
Section: Areas Of Applicationmentioning
confidence: 99%